Trends in the use of benzodiazepine receptor agonists among working-age adults in Belgium from 2004 to 2018 - Colman, Lisa; Delaruelle, Katrijn; Bracke, Piet; Ceuterick, Melissa (Frontiers in Public Health, 2023)
Introduction The use of psychotropics, such as benzodiazepine receptor agonists (BzRAs), among working-age adults in Belgium has shown educational differences. However, it is unclear how work status plays a role in this relationship. Therefore, this research aims to investigate whether work status explains observed educational differences in BzRA use. In addition, considering medicalisation processes, where non-medical factors, such as work status, are increasingly associated with medical mental health care-seeking behavior, this research also aims to investigate whether work status explains observed educational differences in BzRA use, regardless of mental health status. Methods Data are obtained from the Belgian Health Interview Survey (BHIS). Four successive waves are covered: 2004, 2008, 2013, and 2018. The weighted data represent a sample of 18,547 Belgian respondents aged 18 to 65 years old. Poisson regression models are used to analyze the research aims. Time evolutions are plotted using marginal means postestimation. Results The average use of BzRAs shows a slight decline over the waves studied (2004 = 5.99, 2008 = 5.88, 2013 = 5.33, 2018 = 4.31). Educational and work status differences in BzRA use are observed, regardless of mental health status. Individuals with longer education report lower use compared to individuals with shorter education, and individuals who are unemployed, (pre-)retired, or sick or disabled report higher use compared to employed individuals. Furthermore, work status acts as a mediator, partially explaining educational differences in BzRA use, regardless of mental health status. Discussion Work-related uncertainty leads to increased prescribing and medication use, regardless of mental health. Medicalisation and pharmaceuticalisation processes detach social problems from their social roots and treat them as personal failures. The marginalization of the social roots of unemployment, sick leave and involuntary (pre-)retirement has led to a personalization of responsibility. Negative feelings arising from such work statuses may cause isolated, non-specific symptoms for which medical treatment is sought.